Investigation of the Chemical Composition and Dopaminergic Activity of the Vitex Agnus-castus Fruits - G. V. Adamov (Разработка и регистрация лекарственных средств, 2020)
Introduction. Vitex agnus-castus is an important plant in medicine. Extract from its fruits is used as part of drugs for the treatment of premenstrual syndrome.Aim. To study the chemical composition of water-ethanol extract from Vitex fruits, to establish the dopaminergic activity of various extract fractions separated by lipophilicity, as that of its dominant iridoid-agnusideMaterials and methods. The composition of water-ethanol extraction was studied using HPLC-UV and HPLC-MS/MS methods. Identification of the extract components was performed by comparing the retention times on the chromatograms of the test and standard samples. The extract and its fractions were analyzed in vitro using the tyrosine hydroxylase biotest system. Cyclodinone® (oral drops, Vitex agni casti fructuum extract) was used as a reference drug.Results and discussion. Protocatechuic acid, chlorogenic acid, p-hydroxybenzoic acid, agnuside, mizodendron, 6'-O-p-hydroxybenzoylmusaenoside acid, luteolin-7-glucoside, 5-O-caffeoylquinic acid, vitexin, luteolin, apigenin, maslinic acid, corosolic acid and linolenic acid were identified. The liquid extract obtained in the laboratory showed the same activity as Cyclodinone®, ethyl acetate fraction, and agnuside.Conclusion. This work is the most extensive study of the vitex fruit in relation to the nomenclature of identified compounds. The total extract was shown to be more active than any of its fractions proving the synergistic effect of the extract components on the dopamine neurotransmitter system. This observation justifies the feasibility of using the total extract of the vitex fruit. In vitro agnuside demonstrates high dopaminergic activity. This makes it possible to standardize the extract and medicinal plant materials according to the agnuside content.